The effects of sooty mold on photosynthesis and mesophyll structure of mahogany (Swietenia macrophylla King., Meliaceae) - Lemos Filho,José Pires de (2006)
The aim of present study was to evaluate the effects of the sooty mold on anatomy and photochemical activity of mahogany (Swietenia macrophylla) leaves. The photochemical features of shade-developed leaves with or without sooty mold were compared to those of sun leaves using chlorophyll a fluorescence measurements. Leaf anatomy was also evaluated using conventional techniques. The degree of blockage of the photosynthetic active photon flux density (PPFD) by sooty mold and its effect on photochemistry were evaluated. Sun leaves showed thick mesophyll with palisade parenchyma disposed in a uniseriate layer, whereas shade leaves showed narrow mesophyll, independently of sooty mold presence. The effective quantum yield (deltaF/Fm') and the apparent electron transport rate (ETR) of sun leaves were higher than those of shade leaves. The values of ETR suggested that photochemistry saturation occurred at lower PPFD in shade-grown plants. Lower values of the deltaF/Fm' and, consequently, lower values of ETR were observed in leaves with sooty mold. A reduction of 40% of the incident light was seen due to physical blockage by sooty mold which is presumably responsible for an additional decrease of ETR values. Our data indicated that sooty mold did not directly damage the leaf, but reduce leaf photochemistry capacity, by decreasing light availability.